Malignant cells from pleural fluids in malignant mesothelioma patients reveal novel mutations. (May 2018) - Sneddon, Sophie; Dick, Ian; Lee, Y.C. Gary; Musk, A.W. (Bill); Patch, Ann-Marie; Pearson, John V.; Waddell, Nicola; Allcock, Richard J.N.; Holt, Robert A.; Robinson, Bruce W.S.; Creaney, Jenette
Highlights: Tumour cells from mesothelioma pleural effusions contain known driver mutations. Pleural effusion tumour cells contain high frequency mutations in TRAF7, LATS2 . We identified several novel regions of interest in pleural effusion tumour cells. Abstract: Objectives: Malignant mesothelioma (MM) is an asbestos related tumour affecting cells of serosal cavities. More than 70% of MM patients develop pleural effusions which contain tumour cells, representing a readily accessible source of malignant cells for genetic analysis. Although common somatic mutations and losses have been identified in solid MM tumours, the characterization of tumour cells within pleural effusions could provide novel insights but is little studied. Materials and methods: DNA and RNA were extracted from cells from short term cultures of 27 human MM pleural effusion samples. Whole exome and transcriptome sequencing was performed using the Ion Torrent platform. Somatic mutations were identified using VarScan2 and SomaticSniper. Copy number alterations were identified using ExomeCNV in R. Significant copy number alterations were identified across all samples using GISTIC2.0. The association between tumour intrinsic properties and survival was analyzed using the Cox proportional hazards regression model. Results: We identified BAP1, CDKN2A and NF2 alterations in the cells from MM pleural effusions at a higher frequency than what is typically seen in MM tumours from surgical series. The median mutation rate was 1.09 mutations/Mb. TRAF7 and LATS2 alterations were also identified at a high frequency (66% and 59% respectively). Novel regions of interest were identified, including alterations in FGFR3, and the regions 19p13.3, 8p23.1 and 1p36.32. Conclusion: Short term cultures of tumour cells from MM pleural effusions offer an accessible alternative to surgical tumour biopsies in the study of MM genomics and reveal novel mutations of interest. Pleural effusion tumour cells provide an opportunity for the monitoring of tumour dynamics, treatment response and the clonal evolution of MM tumours.